Resting-State Functional Network Topology Alterations of the Occipital Lobe Associated With Attention Impairment in Isolated Rapid Eye Movement Behavior Disorder - Geng, Chaofan; Wang, Shenghui; Li, Zhonglin; Xu, Pengfei; Bai, Yingying; Zhou, Yao; Zhang, Xinyu; Li, Yongli; Zhang, Jiewen; Zhang, Hongju (Frontiers in Aging Neuroscience, 2022)
Purpose This study investigates the topological properties of brain functional networks in patients with isolated rapid eye movement sleep behavior disorder (iRBD). Participants and Methods A total of 21 patients with iRBD (iRBD group) and 22 healthy controls (HCs) were evaluated using resting-state functional MRI (rs-fMRI) and neuropsychological measures in cognitive and motor function. Data from rs-fMRI were analyzed using graph theory, which included small-world properties, network efficiency, network local efficiency, nodal shortest path, node efficiency, and network connectivity, as well as the relationship between behavioral characteristics and altered brain topological features. Results Rey-Osterrieth complex figure test (ROCFT-copy), symbol digital modalities test (SDMT), auditory verbal learning test (AVLT)-N1, AVLT-N2, AVLT-N3, and AVLT-N1-3 scores were significantly lower in patients with iRBD than in HC (P < 0.05), while trail making test A (TMT-A), TMT-B, and Unified Parkinson’s Disease Rating Scale Part-III (UPDRS-III) scores were higher in patients with iRBD (P < 0.05). Compared with the HCs, patients with iRBD had no difference in the small-world attributes (P > 0.05). However, there was a significant decrease in network global efficiency (P = 0.0052) and network local efficiency (P = 0.0146), while an increase in characteristic path length (P = 0.0071). There was lower nodal efficiency in occipital gyrus and nodal shortest path in frontal, parietal, temporal lobe, and cingulate gyrus. Functional connectivities were decreased between the nodes of occipital with the regions where they had declined nodal shortest path. There was a positive correlation between TMT-A scores and the nodal efficiency of the right middle occipital gyrus (R = 0.602, P = 0.014). Conclusion These results suggest that abnormal behaviors may be associated with disrupted brain network topology and functional connectivity in patients with iRBD and also provide novel insights to understand pathophysiological mechanisms in iRBD.